Synthesis and characterisation of chitosan–nitrogen polyphosphonic acid poly(organosiloxane) high temperature proton exchange membranes for fuel cells. (20th March 2016) - Yin, S.; Gao, S.; Shen, C.; Li, W.; Li, H.
Abstract : One kind of acid–base high temperature proton exchange membrane was synthesised from chitosan (CS), 3-aminopropyltriethoxysilane (APTES) and amino trimethylene phosphonic acid (ATMP) by sol–gel process. In order to prevent phosphonic acid from leaching out, ATMP was introduced as proton conductor as well as cross-linker. Fourier transform infrared suggests that the Si–OC2 H5 in APTES appears as a hydrolysis–polycondensation yielding Si–O–Si network, and the introduction of ATMP leads to the protonation of the amino group. These membranes are thermally stable up to ∼180°C and show excellent oxidative stability. In addition, the proton conductivity of CS/APTES/ATMP membranes increases with increasing temperature, reaching the value of 0·0578 S cm − 1 at 140°C under normally anhydrous condition, which indicates that the acid–base pair and hydrogen bond network in CS/APTES/ATMP membranes are favourable to proton transfer.